Effects of matrix types on formation and transformation of energy-accumulating substances in enhanced biological phosphorus removal (EBPR) - Li, D.; Fang, Z.; Long, X.; Tang, R.; Di, S. (Cellular and Molecular Biology, 2016)
Enhanced biological phosphorus removal (EBPR) has been widely used in wastewater treatment. In this study, a laboratory investigation of activated sludge in A/O-SBR reactor was conducted to probe the effects of the matrix types on EBPR polyphosphate, intracellular polysaccharide, polyhydroxyalkanoates (PHA) formation and transformation. There is a decrease in anaerobic condition and an increase in aerobic condition for the intracellular glycogen of sodium propionate matrix and sodium acetate matrix. While the intracellular glycogen of glucose matrix shows a decreasing tendency in both anaerobic and aerobic reaction process. Sodium acetate matrix is beneficial to the formation of polyhydroxybutyrate (PHB), but the content of PHB is relatively small. PHB and poly-3-hydroxyvalerate (PHV) contents in PHA are quite similar in both anaerobic and aerobic reactions with a PHB/PHV ratio of 0.83-1.45. The synthesis of PHV and PHB is mainly in the initial anaerobic stage (0 h - 1 h). Glucose matrix is helpful to the formation of PHV. The content of polymphosphorus shows an increasing tendency in both anaerobic and aerobic stages, suggesting that glucose matrix acclimation of the reactor favors the formation of polymphosphorus.